From Dual Roles to Dynamic Equilibrium: An Overview of Theoretical Perspectives Used in Studies Addressing Work-Life Struggles of Working Mothers - Merve Gerçek (Akademik İncelemeler Dergisi)
There has been much scholarly attention given to the role of women in the labor market throughout the years. While there are plenty of evaluations of ideas and perspectives regarding work-life concepts, there is limited understanding regarding the theoretical foundation of work-life concerns specifically about mothers. This study aims to provide an overview of theories used to investigate the work-life issues of working mothers. The data were collected from the Web of Science database. A total of 63 research studies examining the work-life challenges faced by employed women were evaluated based on theoretical frameworks. It was seen that identity theory and gender perspective are dominant perspectives in the current literature. In addition, the prevailing work-life perspectives adopted in the studies are work-life balance and work-life conflict. The study offers a detailed examination of the various theoretical perspectives employed in understanding the work-life difficulties encountered by employed mothers.